Haptoglobin genotype and cerebrovascular disease incidence in type 1 diabetes. (September 2014) - Costacou, Tina; Secrest, Aaron M; Ferrell, Robert E; Orchard, Trevor J
Objective: We prospectively evaluated the haptoglobin (Hp)–stroke association in type 1 diabetes and hypothesized that despite increasing the risk of coronary artery disease, the presence of the Hp 2 allele would be associated with a lower incidence of stroke. Methods: Participants from the Epidemiology of Diabetes Complications study without prevalent stroke and Hp available were evaluated ( n = 607; mean age 27.6 years and duration 19.3 years). Results: During 22 years of follow-up, stroke incidence did not differ by Hp genotype ( p = 0.49). Restricting analyses to those diagnosed with diabetes ≥1965 (13% mortality vs 40% in the <1965 cohort) to diminish potential survival bias, the adjusted hazard ratio (HR) for Hp 1-1 was 3.08 (95% confidence interval (CI) = 0.81–11.77, p = 0.10). Further stratifying by hypertension prevalence, an increased stroke incidence was observed with Hp 1-1 only in those with hypertension (HR = 7.03, 95% CI = 1.42–34.89, p = 0.02). Conclusion: Despite the protective effect against vascular diabetes complications, a borderline increased risk of stroke was observed with Hp 1-1 in type 1 diabetes. This mixed Hp effect on cardiovascular risk by outcome studied merits further investigation and cautions against the universal application of preventive therapies across all Hp genotypes.